Pengaruh Pemberian Mikrokapsul Minyak Ikan dalam Ransum Puyuh terhadap Performa Produksi - Sestilawarti Sestilawarti; Mirzah Mirzah; Montesqrit Montesqrit (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2013)
An experiment was conducted to determine the effect of feeding fish oil microcapsule on quail performances.  200 quail layers were randomly allocated into 20 pens.  A randomized completely design was used in this study with 0, 2%, 4% and 6% fish oil microcapsule in diet.  Variable measured were feed consumption, egg production, egg weight, mass of egg and feed conversion. Data were analized by CRD and Duncan Multiple Range Test (DMRT).  Results of the experiment indicated that the inclusion of fish oil microencapsule in laying quails diet did not affect the production performances (feed consumption, egg production, egg weight, mass of egg and feed conversion).